1997
DOI: 10.1002/zaac.19976230806
|View full text |Cite
|
Sign up to set email alerts
|

Metallkomplexe von Farbstoffen. VIII Übergangsmetallkomplexe des Curcumins und seiner Derivate

Abstract: Die zweizähnigen Monoanionen von Curcumin[CU, (1,7‐bis(4‐hydroxy‐3‐methoxyphenyl)‐hepta‐1,6‐dien‐3,5‐dion)], Diacetylcurcumin[DACU, (1,7‐bis(4‐acetyl‐3‐methoxyphenyl)‐hepta‐1,6‐dien‐3,5‐dion)], Dihydroxycurcumin[DHCU, (1,7‐bis(4‐hydroxiphenyl)‐hepta‐1,6‐dien‐3,5‐dion)], Dimethylcurcumin[DMCU, (1,7‐bis(3,4‐dimethoxyphenyl)‐hepta‐1,6‐dien‐3,5‐dion)] und Trimethylcurcumin[TMCU, (1,7‐bis(3,4‐dimethoxyphenyl)‐4‐methylhepta‐1,6‐dien‐3,5‐dion] bilden mit den chloroverbrückten Komplexen [(R3P)MCl2]2 (MPd, Pt; RPheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…Orvig et al have reported vanadyl, gallium and indium complexes of curcumin for medicinal applications [7], corroborating the importance of curcumin's free phenolic OH groups for scavenging oxidants and correlated with reduced cytotoxic potential. And curcumin with other transition metals ions Ni 2+ , Zn 2+ , Pd 2+ , Fe 3+ can form strong chelates [8][9][10]. However, studies on Biological activities of the rare earth metal complexes with Curcumin and 1,10-phenanthroline-5,6-dione have been rarely reported.…”
Section: Introductionmentioning
confidence: 97%
“…Orvig et al have reported vanadyl, gallium and indium complexes of curcumin for medicinal applications [7], corroborating the importance of curcumin's free phenolic OH groups for scavenging oxidants and correlated with reduced cytotoxic potential. And curcumin with other transition metals ions Ni 2+ , Zn 2+ , Pd 2+ , Fe 3+ can form strong chelates [8][9][10]. However, studies on Biological activities of the rare earth metal complexes with Curcumin and 1,10-phenanthroline-5,6-dione have been rarely reported.…”
Section: Introductionmentioning
confidence: 97%
“…[16,17]. Also, curcumin with other transition metals ions Ni(II), Zn(II), Pd(II), Fe(III), Cr(III), Mn(II), can form strong chelates [10,[18][19][20]. Curcumin complexes with Zn(II), Cu(II), Mg(II) and Se(II) are synthesized by mechanical mixture, without any conventional organic solvents and found to form complexes with 1:1 for Zn(II), Cu(II) and Mg(II) complexes and 1:2 for Se(II) complex [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the study of the mechanism of their chemiopreventive activity has attracted increasing attention [13][14][15][16][17]. Although b-diketones are known to form complexes with almost every metal, few metal complexes of curcumin and its derivatives have been reported [18], most of which are based on bis M(curc) 2 , M@VO, Cu(II), Ni(II) and Co(II) or tris M(curc) 3 M@Ga(III) and In(III), for evaluation as anticancer agents in vitro and in vivo [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%